PROFITABILITAS SEBELUM DAN SAAT TERJADI COVID-19 PADA PT BANK ACEH SYARIAH - Rauzatul Jannah; Haris Al Amin; Abdul Halim; Syawal Harianto; Abi Waqqash (Jurnal Mahasiswa Akuntansi Samudra, 2023)
The Covid-19 pandemic that emerged in early 2020 had an impact on several sectors in Indonesia, including the banking sector. The consequences of the Covid-19 pandemic had an impact on banking profitability. One of them is PT Bank Aceh Syariah. This study aims to determine differences in profitability values as measured by the ratio of Return On Assets (ROA) and Return On Equity (ROE) at PT Bank Aceh Syariah before and during the Covid-19 pandemic. This research was conducted using quarterly data for 6 years from 2017 to 2022 which was published on the official website of PT Bank Aceh Syariah. The analytical method used in this study is the difference test by testing the hypothesis of the paired sample t test with a significance standard of 0.05. Data processing was carried out using the SPSS analysis tool. The results showed that there was a significant difference in profitability before the pandemic and during the Covid-19 pandemic as measured by the ROA ratio, it was found that profitability before the Covid-19 pandemic and during the Covid-19 pandemic 19 obtained an Asymp value. Sig. (2-tailed) of 0.004, which is more than the specified significance level, which is <0.05. In the ROE ratio, it was found that profitability before the Covid-19 pandemic and during the Covid-19 pandemic obtained an Asymp value. Sig. (2-tailed) of 0.001 which is smaller than the specified significance level, which is <0.05.